2019
DOI: 10.15407/animbiol21.02.021
|View full text |Cite
|
Sign up to set email alerts
|

The impact of twinning and stillbirth on reproductive and economic performance in large Hungarian dairy herds

Abstract: The aim of our study was to quantify the effect of twinning and stillbirth on the main reproductive parameters, and to estimate the resulting economic loss on large-scale commercial dairy farms. The data of 3.660 calvings that occurred on five large Hungarian Holstein-Friesian farms in 2016 and 2017 were analysed retrospectively. Information about twin calvings, stillbirths and uterine treatments were gathered. The main reproductive indices (i.e. calving to conception interval-CCI, services per conception-SPC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Another study, the most recent we found in the literature, ref. [ 26 ] also assessed economic impacts of twin pregnancies in large Hungarian herds and concluded that the overall loss due to a twin pregnancy added $59 per twin pregnancy (1EU = 1.18US$; Table 1 ). This loss was the result of increased calving to conception interval, increased service per conception, reduced conception rate, and increased incidence of retained placenta.…”
Section: Economic Impacts Of Twinningmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study, the most recent we found in the literature, ref. [ 26 ] also assessed economic impacts of twin pregnancies in large Hungarian herds and concluded that the overall loss due to a twin pregnancy added $59 per twin pregnancy (1EU = 1.18US$; Table 1 ). This loss was the result of increased calving to conception interval, increased service per conception, reduced conception rate, and increased incidence of retained placenta.…”
Section: Economic Impacts Of Twinningmentioning
confidence: 99%
“…Ref [ 26 ] analyzed data from 3,660 calvings from five large dairy farms in Hungary through linear and logistic regression and Dunnett test. For the economic analysis, they included losses due to extra days open and excess semen use.…”
Section: Economic Models To Assess Twiningmentioning
confidence: 99%